PERBEDAAN EFEKTIVITAS HEMODIALISA METHODE HD REGULER DENGAN METODE CAPD YANG DILAKUKAN PADA PASIEN GGK DI UNIT HEMODIALISA RSUD Dr. PIRNGADI KOTA MEDAN - Megawati Megawati (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Chronic Kidney Disease (CKD) or chronic kidney failure (CKD) is a condition when kidney function decreases gradually due to kidney damage. Medically, chronic kidney failure is defined as a decrease in the filtering rate of the kidneys for 3 months or more. The kidneys function to filter waste and excess fluid from the blood before being excreted through urine. Every day, the two kidneys filter about 120-150 liters of blood, and produce about 1-2 liters of urine. Within each kidney, there is a filtering unit or nephron which consists of the glomerulus and tubules. The glomerulus filters fluid and waste for excretion, and prevents the exit of blood cells and large molecules of protein. Formulation of the problem: In this study, what is the difference between the effectiveness of the Hemodialysis Regular Hemodialysis Method and the CAPD Method in CRF Patients in the Hemodialysis Unit of RSUD Dr. Pirngadi, Medan City. Research Objectives: to determine the effectiveness of Hemodialysis between the HD Regular method and the CAPD method in reducing urea and creatinine levels in CRF patients at the Hemodialysis Unit of RSUD Dr. Pirngadi City of Medan in 2020. This type of research is analytic, namely to find out the difference in the effectiveness of the Hemodialysis Regular HD Method and the CAPD Method in CKD Patients in the Hemodialysis Unit of RSUD Dr. Pirngadi, Medan City. The design used in this study is cross-sectional, that is, different populations are observed at the same time for all the same variables in order to save time and money, with a total sample of 60 people. The results of this study describe the effectiveness of reducing urea creatinine levels before and after HD Regular as well as reducing urea creatinine levels before and after HD CAPD. Conclusion : The HD CAPD method is more effective than the HD Regular method in reducing urea creatinine in patients with chronic kidney failure (CKD). HD CAPD is more effective when viewed from a decrease in urea creatinine levels where HD regular before regular HD obtained p value = 0.069 and before HD CAPD p value = 0.000. It is recommended: for patients with Chronic Renal Failure to know HD CAPD and excess CAPD is more effective in reducing urea and creatinine levels.